Optical Spectroscopy of young brown dwarfs in Orion - Riddick, F; Roche, P; Lucas, P (2003)
Red spectra of a sample of low-mass stars and brown dwarfs in the Orion Trapezium cluster are discussed. They show late-type spectral characteristics confirming cluster membership and some show evidence of circumstellar activity.